Cold stress resilience of Iranian olive genetic resources: evidence from autochthonous genotypes diversity - Karamatlou, Issa; Navabpour, Saeid; Nezhad, Khalil Zaynali; Mariotti, Roberto; Mousavi, Soraya; Hosseini-Mazinani, Mehdi (Frontiers in Plant Science, 2023)
Abstract Olive (Olea europaea L.) is one of the most cultivated tree species in Iran. This plant is characterized by its tolerance to drought, salt, and heat stresses, while being vulnerable to frost. During the last decade, periods of frost have occurred several times in Golestan Province, in the northeast of Iran, which caused severe damage to olive groves. This study aimed to evaluate and individuate autochthonous Iranian olive varieties with regard to frost tolerance and good agronomic performance. For this purpose, 218 frost-tolerant olive trees were selected from 150,000 adult olive trees (15-25 years old), following the last harsh autumn of 2016. The selected trees were reassessed at different intervals, i.e. one, four and seven months after the cold stress in field conditions. Using nineteen morpho-agronomic traits, 45 individual trees with relatively stable frost-tolerance were reevaluated and selected for this research. Ten highly-discriminating microsatellite markers were used for the genetic profiling of the 45 selected olive trees, and ultimately five genotypes with the highest tolerance among 45 selected ones were placed in a cold room at freezing temperatures for image analyses of cold damage. The results of morpho-agronomic analyses evidenced no bark splitting or symptoms of leaf drop in the 45 cold-tolerant olives (CTOs). The oil content of the cold-tolerant trees comprised almost 40% of the fruit dry weight, highlighting the potential of these varieties for oil production. Moreover, through molecular characterization, 36 unique molecular profiles were individuated among the 45 analyzed CTOs which were genetically more similar to the Mediterranean olive cultivars than the Iranian ones. The present study demonstrated the high potential of local olive varieties, which would be promising and more suitable than commercial olive varieties, with regard to the establishment of olive groves under cold climate conditions. This could be a valuable genetic resource for future breeding activities to face climate changes.